Nasal fibroblast conditioned medium promotes cell attachment and migration of human respiratory epithelium - Rohaina Che Man,; Yogeswaran Lokanathan,; Rabiatul Adawiyah Razali,; Shiplu Roy Chowdury,; Aminuddin Saim,; Ruszymah Hj Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Endoscopic sinus surgery (ESS) is a well-known surgical treatment for chronic rhinosinusitis disease after failed medical and antibiotics treatment. However, improper wound healing might induce synechiae or adhesion. Conditioned medium from cultured cells is known to promote wound healing and potentially able to accelerate wound healing in ESS and other airway epithelial injuries. This study was to investigate the effect of human nasal fibroblast conditioned medium on the attachment, proliferation and migration of respiratory epithelial cells (RECs) in an in vitro model. RECs and fibroblasts were co-cultured in Defined Keratinocytes Medium and F-12 and Dulbecco’s Modified Eagle’s Medium. Once confluent, the fibroblasts were removed, leaving the colonies of RECs to reach confluency. RECs and fibroblasts were cultured separately and the conditioned medium was acquired by culturing fibroblast either in DKSFM or F12: DMEM, denoted as NFCM_DKSFM and NFCM_FD, respectively. RECs were supplemented with 20% conditioned medium for attachment, proliferation and migration assay. The results showed significantly higher cell attachment in NFCM_DKSFM (3452.77±588.1 cell/cm2) compared to NFCM_FD (2336.1±440.4 cell/cm2) and DKSFM alone (2819.8±509.5 cell/cm2). After 7 days, the specific growth rate was higher in DKSFM (0.019±5.16×10-4 h-1) compared to NFCM_DKSFM (0.015±8.94×10-4 h-1) and NFCM_FD (0.013±1.03×10-3 h-1). The mean of migration rate was significantly higher in NFCM_DKSFM (4341.81±385.7 μm2/hr) compared to NFCM_FD (1803.38±408.1 μm2/hr) and DKSFM (1933.48±271.9 μm2/hr). Hence, NFCM_DKSFM supplementation provides suitable culture conditions for RECs through increased cell attachment and migration, which suggest that the factors secreted in conditioned medium may play a major role in enhancing airway epithelial wound healing.